Changing students' beliefs about the relevance of mathematics in an advanced secondary mathematics class. Issue 1 (2nd January 2020) - Gijsbers, Dié; de Putter-Smits, Lesley; Pepin, Birgit
ABSTRACT: This study shows that using authentic contexts for learning differential equations in a differentiation-by-interest setting can enhance students' beliefs about the relevance of mathematics. The students in this study were studying advanced mathematics (wiskunde D) at upper secondary school in the Netherlands. These students are often not aware of the relevance of the mathematics they have to learn in school. More insights into the application of mathematics in other sciences can be beneficial for these students in terms of preparation for their future study and career. A course differentiating by student interest with new context-rich curriculum materials was developed in order to enhance students' beliefs about the relevance of mathematics. The intervention aimed at teaching differential equations through guided small-group tasks in scientific, medical or economical contexts. The results show that students' beliefs about the relevance of mathematics improved, and they appreciated experiencing how the mathematics was applied in real-life situations.